MORN1 has a conserved role in asexual and sexual development across the apicomplexa. - Ferguson, D; Sahoo, N; Pinches, R; Bumstead, J; Tomley, F; Gubbels, M (2008)
The gene encoding the membrane occupation and recognition nexus protein MORN1 is conserved across the Apicomplexa. In Toxoplasma gondii, MORN1 is associated with the spindle poles, the anterior and posterior rings of the inner membrane complex (IMC). The present study examines the localization of MORN1 during the coccidian development of T. gondii and three Eimeria species (in the definitive host) and erythrocytic schizogony of Plasmodium falciparum. During asexual proliferation, MORN1 is associated with the posterior ring of the IMCs of the multiple daughters forming during T. gondii endopolygeny and schizogony in Eimeria and P. falciparum. Furthermore, the expression of P. falciparum MORN1 protein peaked in late schizogony. These data fit a model with a conserved role for MORN1 during IMC assembly in all variations of asexual development. An important new observation is the reactivity of MORN1 antibody with certain sexual stages in T. gondii and Eimeria species. Here MORN1 is organized as a ring-like structure where the microgametes bud from the microgametocyte while in mature microgametes it is present near the flagellar basal bodies and mitochondrion. These observations suggest a conserved role for MORN1 in both asexual and sexual development across the Apicomplexa.